2022
DOI: 10.1155/2022/8215214
|View full text |Cite|
|
Sign up to set email alerts
|

Study on the Global Stability for a Generalized SEIR Epidemic Model

Abstract: In the current study, a generalized SEIR epidemic model is studied. The generalized fractional-order SEIR model (susceptible-infected-recovered (SIR) epidemic) model differentiated the population into susceptible population, exposure population, infected population, and rehabilitation population and has fundamental mentoring importance for the forecast of the probable outburst of infectious ailments. The fundamental duplicated quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Otherwise the algorithm thinks it is a virus. Based on the above strategy, a new compartment was introduced on the basis of the classical Susceptible-Exposed-Infected-Recovered (SEIR) model [6,7]: the contained node (Contained, C), and this new mechanism was named Susceptible-Exposed-Contained-Infected-Infected-Recovered (Susceptible-Exposed-Contained-Infected-Recovered, SECIR). The contained node will detect the nodes in it by the log information carried by the ids intrusion detection system.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise the algorithm thinks it is a virus. Based on the above strategy, a new compartment was introduced on the basis of the classical Susceptible-Exposed-Infected-Recovered (SEIR) model [6,7]: the contained node (Contained, C), and this new mechanism was named Susceptible-Exposed-Contained-Infected-Infected-Recovered (Susceptible-Exposed-Contained-Infected-Recovered, SECIR). The contained node will detect the nodes in it by the log information carried by the ids intrusion detection system.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%